Lestaurtinib Has the Potential to Inhibit the Proliferation of Hepatocellular Carcinoma Uncovered by Bioinformatics Analysis and Pharmacological Experiments - Wu, Shuang; Liu, Shihai; Li, Yan; Liu, Changchang; Pan, Huazheng (Frontiers in Cell and Developmental Biology, 2022)
Patients diagnosed with hepatocellular carcinoma (HCC) seek a satisfactory prognosis. However, most HCC patients present a risk of recurrence, thus highlighting the lack of effectiveness of current treatments and the urgent need for improved treatment options. The purpose of this study was to identify new candidate factors in the STAT family, which is involved in hepatocellular carcinogenesis, and new targets for the treatment of HCC. Bioinformatics web resources, including Oncomine, Gene Expression Profiling Interactive Analysis (GEPIA), The Human Protein Atlas (HPA), Tumor Immune Estimation Resource (TIMER) and GSCALite, were used to identify candidate genes among the STAT family in HCC. STAT1 is significantly overexpressed in hepatocellular carcinoma. More meaningfully, high STAT1 expression was significantly associated with poor prognosis. Therefore, STAT1 is expected to be a therapeutic target. The JAK2 inhibitor lestaurtinib was screened by a Genomics of Cancer Drug Sensitivity Project (GDSC) analysis. Pharmacological experiments showed that lestaurtinib has the ability to prevent cell migration and colony formation from single cells. We also found that STAT1 is involved in inflammatory responses and immune cell infiltration. Immune infiltration analysis revealed a strong association between STAT1 levels and immune cell abundance, immune biomarker levels, and immune checkpoints. This study suggests that STAT1 may be a key oncogene in hepatocellular carcinoma and provides evidence that the JAK2 inhibitor lestaurtinib is a potent antiproliferative agent that warrants further investigation as a targeted therapy for HCC.